Linking Cognitive Style and Organizational Behavior Through Self-Efficacy: A Theoretical Investigation - Wang, Rui; Mahmood, Nik Hasnaa Nik (Archives of Business Research, 2025)
This literature review explores the multifaceted role of self-efficacy in leadership, employee behavior, and organizational performance, drawing primarily on Bandura’s (1997) social learning theory. Two types of self-efficacy—high and low—are discussed in the context of leadership effectiveness. Leaders with high self-efficacy exhibit goal orientation, resilience, and positive communication, which significantly enhance team motivation and organizational success. In contrast, low self-efficacy is associated with avoidance of responsibility, task delegation, and negative attitudes, often leading to reduced employee performance. The review also highlights the mediating role of self-efficacy in the relationship between organizational factors and innovative work behavior (IWB). Empirical evidence suggests that self-efficacy significantly influences innovative intentions and actions, with autonomy, past success, and learning experiences contributing to its development. Cognitive style, particularly analytic versus intuitive, further shapes self-efficacy across stages of entrepreneurial behavior. Moreover, leadership styles and organizational climates that support autonomy and creativity strengthen employees’ self-belief and motivation. The review concludes that self-efficacy is not only a predictor of leadership success but also a vital mediator influencing job satisfaction, innovation, and organizational citizenship behavior. The findings underscore the importance of fostering self-efficacy through supportive leadership, experience, and reflective practices, while cautioning against authoritarian approaches that diminish employee confidence and engagement. This review contributes to the understanding of how self-efficacy shapes individual and organizational outcomes within dynamic work environments.